2014
DOI: 10.4172/2332-0702.1000145
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health of Children and Adolescents in Da Nang

Abstract: This is a cross-sectional epidemiological study comprising 840 randomly selected children in the age groups of 3, 5, 10 and 15 year olds. All children were clinically examined for number of teeth, dental caries, dental fillings, plaque, gingivitis and probing pocket depth. Dental care and dietary habits were collected using a self-reported questionnaire. Among 3 and 5 year olds, 98% suffered from dental caries, compared to 91% of 10 and 15 year olds. The mean (SD) of decayed (initial and manifest) and filled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…4). Previously done studies have shown that male children had poor oral hygiene when compared to female children [30]. This is similar to our findings where female patients with stainless steel crowns had good oral hygiene when compared to male children with stainless steel crowns [31].…”
Section: Resultssupporting
confidence: 92%
“…4). Previously done studies have shown that male children had poor oral hygiene when compared to female children [30]. This is similar to our findings where female patients with stainless steel crowns had good oral hygiene when compared to male children with stainless steel crowns [31].…”
Section: Resultssupporting
confidence: 92%
“…Early childhood caries (ECC) is more common among children living in areas with low Socioeconomic Status (SES) than among children in areas with higher SES [1][2][3]. The same pattern has been found in Region Östergötland in Sweden, where also an increasing difference in ECC prevalence between areas with low and high SES recently has been found [4,5]. ECC is however at large preventable and previous studies have shown that early prevention and parental education in oral health behaviors provide the best conditions for improvement in children's oral health [6][7][8].…”
Section: Introductionmentioning
confidence: 86%
“…The intervention group was recruited consecutively from January 1, 2013 to December 31, 2014 using the following inclusion criteria: pregnant woman visiting the MHS for the first time in their current pregnancy and living in one of two low-SES areas in a city in Southeast of Sweden. SES was defined as the proportion of high-income individuals living in each very small area of the municipality of the specified the city [5].…”
Section: Study Groupsmentioning
confidence: 99%
See 2 more Smart Citations